THE STRATEGIES OF WOMEN PROTECTION IN SOLVING DOMESTIC VIOLENCE CASES IN CENTRAL JAVA THROUGH SHELTERED HOUSE - Suteki Suteki; Ani Purwanti (Fakultas Hukum, Universitas Diponegoro, 2016)
Domestic Violence is a highly occured violence which is pervasively victimizing women. Several study show that in the handling process, women, as the victim of domestic violence, has difficulty to go back home, which means she is going to face tortures again by her husband in her house. The problems are: the protection of women in eradicating Domestic Violence in Central Java and; and the ideal protection for women in solving Domestic Violence through Sheltered house. this research uses Socio-Legal method. The existence of sheltered house can become the alternative to protect the victimized women and handle the domestic violence whether in the family sphere or in the public sphere.The increasing number of women as the victim of violence time by time is spreading to the small city but based on the data of 35 regencies and cities in Central Java, only 7 areas which have sheltered house. Keywords: Sheltered House, Domestic Violence, Central Java